Work Domain Analysis for understanding medication safety in care homes in England: an exploratory study. Issue 1 (2nd January 2016) - Lim, Rosemary H.M.; Anderson, Janet E.; Buckle, Peter W.
Abstract : Medication safety and errors are a major concern in care homes. In addition to the identification of incidents, there is a need for a comprehensive system description to avoid the danger of introducing interventions that have unintended consequences and are therefore unsustainable. The aim of this study was to explore the impact and uniqueness of Work Domain Analysis (WDA) to facilitate an in-depth understanding of medication safety problems within the care home system and identify the potential benefits of WDA to design safety interventions to improve medication safety. A comprehensive, systematic and contextual overview of the care home medication system was developed for the first time. The novel use of the abstraction hierarchy (AH) to analyse medication errors revealed the value of the AH to guide a comprehensive analysis of errors and generate system improvement recommendations that took into account the contextual information of the wider system. Abstract : Practitioner Summary: It is widely acknowledged that a systems approach is necessary to improve medication safety. This study used a cognitive engineering method, Work Domain Analysis, to map the care home medication system and analyse medication errors. A macro-level view of the system was developed and this has provided a knowledge base for future interventions.